Economic evaluation of first-line and maintenance treatments for advanced non-small cell lung cancer: a systematic review - Chouaïd C; Crequit P; Borget I; Vergnenegre A (Dove Medical Press, 2014)
Christos Chouaïd,1 Perinne Crequit,2 Isabelle Borget,3 Alain Vergnenegre4 1Service de Pneumologie et de Pathologie Professionnelle, Centre Hospitalier Intercommunal Créteil et Université de Paris Est Créteil, Paris, France; 2Service de Pneumologie, Hôpital Tenon, Assistance Publique-Hôpitaux de Paris, Paris, France; 3Service de Biostatistique et d’Epidémiologie, Institut Gustave Roussy, Villejuif, France; 4Unité d’Oncologie Thoracique et Cutanée, Centre Hospitalier Universitaire Limoges, Limoges, France Abstract: During these last years, there have been an increased number of new drugs for non-small cell lung cancer (NSCLC), with a growing financial effect on patients and society. The purpose of this article was to review the economics of first-line and maintenance NSCLC treatments. We reviewed economic analyses of NSCLC therapies published between 2004 and 2014. In first-line settings, in unselected patients with advanced NSCLC, the cisplatin gemcitabine doublet appears to be cost-saving compared with other platinum doublets. In patients with nonsquamous NSCLC, the incremental cost-effectiveness ratios (ICERs) per life-year gained (LYG) were $83,537, $178,613, and more than $300,000 for cisplatin-pemetrexed compared with, respectively, cisplatin-gemcitabine, cisplatin-carboplatin-paclitaxel, and carboplatin-paclitaxel-bevacizumab. For all primary chemotherapy agents, use of carboplatin is associated with slightly higher costs than cisplatin. In all the analysis, bevacizumab had an ICER greater than $150,000 per quality-adjusted life-year (QALY). In epidermal growth factor receptor mutated advanced NSCLC, compared with carboplatin-paclitaxel doublet, targeted therapy based on testing available tissue yielded an ICER of $110,644 per QALY, and the rebiopsy strategy yielded an ICER of $122,219 per QALY. Compared with the triplet carboplatin-paclitaxel-bevacizumab, testing and rebiopsy strategies had ICERs of $25,547 and $44,036 per QALY, respectively. In an indirect comparison, ICERs per LYG and QALY of erlotinib versus gefitinib were $39,431 and $62,419, respectively. In anaplastic lymphoma kinase-positive nonsquamous advanced NSCLC, the ICER of first-line crizotinib compared with that of chemotherapy was $255,970 per QALY. For maintenance therapy, gefitinib had an ICER of $19,214 per QALY, erlotinib had an ICER of $127,343 per LYG, and pemetrexed had an ICER varying between $183,589 and $205,597 per LYG. Most recent NSCLC strategies are based on apparently no cost-effective strategies if we consider an ICER below $50,000 per QALY an acceptable threshold. We need, probably on a countrywide level, to have a debate involving public health organizations and pharmaceutical companies, as well as clinicians and patients, to challenge the rising costs of managing lung cancer. Keywords: lung cancer, costs, economics, cost-effectiveness, evaluation